2017
DOI: 10.1038/s41467-017-00597-2
|View full text |Cite
|
Sign up to set email alerts
|

The brain is required for normal muscle and nerve patterning during early Xenopus development

Abstract: Possible roles of brain-derived signals in the regulation of embryogenesis are unknown. Here we use an amputation assay in Xenopus laevis to show that absence of brain alters subsequent muscle and peripheral nerve patterning during early development. The muscle phenotype can be rescued by an antagonist of muscarinic acetylcholine receptors. The observed defects occur at considerable distances from the head, suggesting that the brain provides long-range cues for other tissue systems during development. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 66 publications
2
47
1
Order By: Relevance
“…[32][33][34][35] Moreover, reinforcing these endogenous membrane voltage patterns rescues eye and brain defects caused by mutant notch and teratogen nicotine. 34,42,43 These experiments show that the bioelectric prepattern is necessary and sufficient for normal eye and brain morphogenesis as well as normal expression of the patterning genes.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…[32][33][34][35] Moreover, reinforcing these endogenous membrane voltage patterns rescues eye and brain defects caused by mutant notch and teratogen nicotine. 34,42,43 These experiments show that the bioelectric prepattern is necessary and sufficient for normal eye and brain morphogenesis as well as normal expression of the patterning genes.…”
Section: Introductionmentioning
confidence: 84%
“…[31][32][33][34][35]68 Reinforcing correct bioelectrical signals has been shown to rescue neural patterning defects caused by aberrant notch signals, mechanical damage, or exposure to neuro-teratogens such a nicotine. 34,42,43 Our previous work has extended the use of optogenetics to embryonic and regenerating tissues to more accurately control the timing and location of bioelectric intervention, 47,48 thus increasing our resolution as we study the intertwining of bioelectric events with second messengers and genetic regulatory networks. Building on these findings, we investigated optogenetic modulation of bioelectric signals for rescue of brain and eye malformations in a Xenopus model of fetal alcohol syndrome disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of neural control systems from pre-neural morphogenetic mechanisms suggests that there should be a lot of interplay between these systems in development. The requirement of a functional CNS for effective organ regeneration (Brockes, 1987) and for correct patterning in development (Herrera-Rincon et al, 2017;Herrera-Rincon and Levin, 2018) has been shown in a range of model species, and the tools of optogenetics can now be used to dissect the information content of nerve-mediated signaling as instructive cues for both normal morphogenesis and regulative development in which bodies adapt to major changes in architecture (Oviedo et al, 2010). 10.…”
Section: Predictions and Research Programmentioning
confidence: 99%
“…Critically, such discussions are often stymied by the desire to assign a single, reliable cause to a complex and stochastic fetal phenotype. Policy and pharmacological regulations would be revolutionized by a more nuanced, multifactorial notion of causation that replaced a binary expectation of cause and effect with the one that took into account the differential ability of some embryos to resist teratogens and the factors (like nervous system activity) that contributed to that capability.…”
Section: Evolving Concepts: the Future Of Finding And Exploiting Biolmentioning
confidence: 99%